A duality theorem for the ic-resurgence of edge ideals. (March 2023) - Villarreal, Rafael H.
Abstract: The aim of this work is to use linear programming and polyhedral geometry to prove a duality formula for the ic-resurgence of edge ideals. We show that the ic-resurgence of the edge ideal I of a clutter C and the ic-resurgence of the edge ideal I ∨ of the blocker C ∨ of C coincide. If C is the clutter of bases of certain uniform matroids, we recover a formula for the resurgence of I, and if C is a connected non-bipartite graph with a perfect matching, we show a formula for the Waldschmidt constant of I ∨ .